Synthesis of novel flexible tamoxifen analogues to overcome CYP2D6 polymorphism and their biological evaluation on MCF‐7 cell line. Issue 4 (9th January 2020) - Ahmed, Nermin S.; Wober, Jannette
Abstract: Tamoxifen (TAM) is currently the endocrine treatment of choice for all stages of breast cancer; it has proven success in ER positive and ER negative patients. TAM is activated by endogenous CYP450 enzymes to the more biologically active metabolites 4‐hydroxytamoxifen and endoxifen mainly via CYP2D6 and CYP3A4/5. CYP2D6 has been investigated for polymorphism; there is a large interindividual variation in the enzyme activity, this drastically effects clinical outcomes of tamoxifen treatment. Here in we report the design and synthesis of 10 novel compounds bearing a modified tamoxifen skeleton, ring C is substituted with different ester groups to bypass the CYP2D6 enzyme metabolism and employ esterase enzymes for activation. All compounds endorse flexibility on ring A . Compounds (II–X ) showed MCF‐7% growth inhibition >50% at a screening dose of 10 μM. These results were validated by yeast estrogen screen (YES) and E‐Screen assay combined with XTT assay. Compound II ( E/Z 4‐[1–4‐(3‐Dimethylamino‐propoxy)‐phenyl)‐3‐(4‐methoxy‐phenyl)‐2‐methyl‐propenyl]‐phenol) showed nanomolar antiestrogenic activity (IC50 = 510 nM in YES assay) and was five times more potent in inhibiting the growth of MCF‐7 BUS (IC50 = 96 nM) compared to TAM (IC50 = 503 nM). Esterified analogues VI, VII were three times more active than TAM on MCF‐7 BUS (IC50 = 167 nM). Novel analogues are prodrugs that can ensure equal clinical outcomes to all breast cancer patients. Abstract :